2017
DOI: 10.1177/1359105317739965
|View full text |Cite
|
Sign up to set email alerts
|

Why do they do it? Assessing self-report physical activity behavior and quality of life in individuals with multiple sclerosis

Abstract: Physical activity has been shown to effectively aid multiple sclerosis symptom management; however, individuals with multiple sclerosis tend to be inactive physically. Developing effective, sustainable, physical activity interventions involves first understanding motivators for physical activity. Open-ended surveys exploring physical activity motivators were collected from 215 individuals with multiple sclerosis. Responses indicate that self-efficacy and internalized motivation derived from physical activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
3
1
2
Order By: Relevance
“…Other studies have also highlighted the association between more autonomous motivation and greater PA in this group. [20][21][22] Although these findings are important to our understanding of PA behavior in adults with MS, it is also necessary to understand how motivation becomes more autonomous. From an SDT perspective, the degree to which an individual's motivation will be more autonomously regulated depends, in part, on the existing social context.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also highlighted the association between more autonomous motivation and greater PA in this group. [20][21][22] Although these findings are important to our understanding of PA behavior in adults with MS, it is also necessary to understand how motivation becomes more autonomous. From an SDT perspective, the degree to which an individual's motivation will be more autonomously regulated depends, in part, on the existing social context.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…40,41 Instead, it is likely that participants in this study reflected a more autonomous and self-endorsed willingness to be physically active because of its personal value and utility. 17 Physical activity engagement in this group often centers around meeting goals of improved disease management and overall health 21 rather than on the expectations of others or because it is inherently pleasurable.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Gating of ORAI1 by STIM1 is mainly governed by a primary interaction of the STIM1 CAD/SOAR domain with the C-terminus of ORAI1 and potentially directly with the "nexus" site (amino acids 261-265 of ORAI1 30 ). This site elicits a conformational transduction pathway via transmembrane domain TM4→ TM3→ TM1 helix to open the pore (reviewed recently in 4,31 ). However, several groups have suggested that the CAD domain also interacts with the Extended Transmembrane Orai1 N-terminal (ETON) region (aa 73-90) [ [32][33][34] and that this region is critical for gating as well as fast Ca 2+ dependent inactivation.…”
Section: Domain a Interferes With Full Gating Of Orai1mentioning
confidence: 99%
“…(автор John E. Ware). Выделенные восемь факторов качества жизни, которые чаще всего измеряются и изменяются в процессе исследования, были определены как основные критерии [7].…”
unclassified